Nonadjunctive Use of Continuous Glucose Monitors for Insulin Dosing: Is It Safe? - Shapiro, Alan R. (Journal of diabetes science and technology, 2017)
With the increasing accuracy of continuous glucose monitors (CGM) have come calls for the Food and Drug Administration (FDA) to label these devices as safe for nonadjunctive dosing of insulin. However, there is evidence that these devices are subject to sporadic, unpredictable, large errors. A text analysis of reports to the FDA MAUDE database since 2015 reveals over 25 000 complaints of CGM sensor inaccuracy, with instances directly leading to serious outcomes. These new data were not considered at a recent FDA Advisory Panel meeting that voted to approve Dexcom G5 relabeling for nonadjunctive use. Social media is another source of surveillance data providing evidence of large CGM inaccuracies in real-world use. We need to improve safety procedures, not remove them. CGMs offer unique information and alerts for managing diabetes, but the issue is not whether they are better than other approaches to monitoring glucose, but how they can be best used in conjunction with devices that offer the confirmatory readings needed for patient safety.